Raul simplified the expression, as shown below.

–[3h + 7h(2 – h)] = –[10h(2 – h)] = –[20h – h] = –19h

Describe the error(s) in Raul’s work.

Respuesta :

Answer:

Raul's errors are in the application of the distributive property(he applied it wrongly), in not respecting the precedence of operations, and in the multiplication of two terms with the same base(we add the exponent).

Step-by-step explanation:

Distributive property:

The distributive property of multiplication is:

a*(b + c) = a*b + a*c

Precedence of operations:

First multiplication, then addition.

Multiplication of terms with the same base:

The multiplication of h*h = h², which Raul missed.

The correct simplification is given by:

[tex]-[3h + 7h(2-h)] = -[3h + 14h - 7h^2] = -[17h - 7h^2]=7h^2 - 17h[/tex]

Answer:

he should have  worked out 7h(2 - h) first before adding the 3h. (first step)

2nd step he multiplied the 2 by -10h  but he also should have multiplied the -h by the -10h ( Distributive law)

Step-by-step explanation:

Got it right on edge